TAG QUESTIONS IN BRITISH NEWS INTERVIEW - Dianita Damayanti (Jurnal Sastra - Studi Ilmiah Sastra, 2021)
This research focuses on the types and functions of tag questions and how discourse participants use tag question for doing and displaying alignment and disalignment. A descriptive interpretative research method is used to analyze the data. There are four dialogues that the writer used to find data. They are drawn from Hardtalk, news programme shown on BBC World News and the BBC News Channel. From the analysis, the writer finds that the auxiliary in the tag agrees with the tense, aspect, and modality of the auxiliary verb in the anchoring clause. The polarity value of the preceding anchoring clause also affects that of the tag question: when the main clause is positive, the tag question is negative, and vice versa. The pronoun in the tag also agrees with the person, number, and gender value of the main clause’s subject. There are two main functions of tag questions in British news interviews, confirmation and challenge. Discourse participants use tag questions both for inviting alignment, such as requesting confirmation and for doing disalignment actions such as challenges and disagreement.